A radio bypass [wireless broadband]. - Cherry, S.
This paper explains why Malaysian Internet service provider, Jaring, is creating a 1-megabit per second wireless service in an attempt to compete better with the national carrier, Telekom Malaysia Berhad. Jaring aims to provide a wireless equivalent to DSL that can also carry high-quality telephone calls. While Jaring's transformation from mere service provider to network operator comes with considerable risks, the potential rewards are too great to ignore and the risks of doing nothing are greater still. To mitigate the risks, however, Jaring chose equipment that can operate on a variety of spectral bands and should be able to weather the storms of technological change.
Keywords: 3G cellular technology; Jaring; Malaysian Internet service; Soma Network Inc; WiMax; Licensed radio spectrum; Network operator; Radio bypass; Risks mitigation; Wireless broadband; Wireless connections